ANALISIS BEBAN KERJA PUBLIC AREA ATTENDANT DI HOTEL ARYADUTA PEKANBARU - Simbolon, Herikson H; Ibrahim, Mariaty (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
This research aims to determine the right number of employees which is Public Area Attendant ideal workload handled at Aryaduta Hotel Pekanbaru.This research was used descriptive quantitative method toexamined the issues. The sample in this research are 5 people and used census method. Data collection techniques in this study used observation, interviews and documentation. This research was used the exponent determinants technique (exponential smoothing), with two exponents in the human resources planning which consists of exponents workload in producing a product, as an analysis of the workload (work load analysis) and exponent of time (cycle time) to complete a product and to find the number of employees or staff that were ideal.Based on the research that has been done, for the whole of the results and from the calculation of ideal working time for the Public Area Attendant still need 1 person, that number must be filled by Aryaduta Hotel to cover their staff workload.Keywords: Workload, Public Area Attendant, Number of Ideal Employees